Drug Information Service during Covid-19 Pandemic - Sherly Tandi Arrang; Reynelda Juliani Sagala; Dion Notario; Erlia Anggrainy Sianipar; Fonny Cokro (Institute for Research and Community Services, 2021)
Pharmacists and pharmaceutical personnel need to support improving the people’s quality of life during the covid-19 outbreak by providing pharmaceutical services, one of which is the Drug Information Service (PIO). Many regions in Indonesia, including DKI Jakarta, have placed large-scale social restrictions since March 2020. In connection with that, the Department of Pharmacy of Atma Jaya Catholic University of Indonesia (PSFUAJ) organized an online PIO program. This program aimed to provide the service of Covid-19 drug-related information and education to the community. The PIO was carried out from April to July 2020 via whatsapp, email, and telephone. In addition, health education was provided through e-flyers, published on Instagram @pio_farmasi_uaj. Eighty percent of the questions were submitted via whatsapp, while the rest was sent via email. Most of the questions submitted (80%) were categorized into self-edication. Further examination shows that the common questions were related to drug choice (27.78%). These data indicate that most questioners tend to provide self-medication first and that they will only see a doctor if they have not recovered or experienced any improvement. PSFUAJ will continue running this program and disseminating this program to a broader audience.